Effectiveness of Structured Teaching on Immunization Knowledge and Attitude Among Mothers of Children Under-5 years of Age at Bal Mahila Chikitsalaya, Lucknow - Smrati Shukla; Ayushi Shukla (International Journal of Children, 2024)
This section offers a thorough overview of the study's background, explaining the significance of vaccination, the variables affecting vaccination coverage, the role mothers play in the decision-making process regarding vaccinations, and the necessity of focused interventions to improve immunization uptake among children under five. As a fundamental component of preventive healthcare, immunization shields both individuals and communities from a variety of infectious diseases. In order to comprehensively assess changes in mothers' knowledge and attitudes about vaccinations after the structured instruction program, the study uses a quantitative research approach and to evaluate the efficacy of the intervention, data from eligible women will be gathered both before and after it is using a pretest-posttest approach. 75 mothers of children under five from the BMC Turiaganj neighbourhood in Lucknow will be chosen for the study using a systematic random sampling technique. The purpose of this study was to evaluate how well a structured training program at Bal Mahila Chikitsalaya in Turiaganj, Lucknow affected the knowledge and attitudes of mothers of children under five about vaccinations. The initiative was created to close information gaps and change negative attitudes in order to increase the number of people who have received vaccinations. The results showed that after the intervention, there had been a considerable increase in both knowledge and attitudes. Mothers had an enhanced comprehension of the significance, timeliness, and advantages of vaccination, along with particular vaccinations such as those for tuberculosis and Hepatitis B. The success of the program in improving maternal understanding and perceptions of immunization is demonstrated by the rise in correct responses and positive sentiments across the majority of survey items. Even with the generally favorable results, certain obstacles still exist. Persistent myths about serious side effects and a gender bias that favors boys over girls when it comes to vaccinations highlight the necessity for ongoing education initiatives. These results imply that although formal training programs are beneficial, they should only be used as a component of a longer-term, all-encompassing plan that also involves community involvement, continual education, and focused interventions to address particular issues.
Keywords: Children under five; Intervention; Systematic random sampling; immunization; mothers; vaccination